The value of placental vascularization indices for predicting preeclampsia and fetal growth restriction in different stages of gestation: A prospective and longitudinal study. (May 2022) - Chen, J.Y.; Chen, M.; Wu, X.J.; Sun, J.M.; Zhang, Y.; Li, Y.F.; Zhong, L.Y.; Yu, B.L.; Luo, J.; Liu, J.H.
Abstract: Introduction: To assess value of placental vascularization indices (PVIs) for predicting preeclampsia (PE) and fetal growth restriction (FGR) in different stages of pregnancy in high-risk women. Method: PVIs derived from 3-dimensional power doppler(3DPD) imaging were measured at seven stages of pregnancy: 11–13 +6 w, 15–19 +6 w, 20–23 +6 w, 24–27 +6 w, 28–31 +6 w, 32–36 +6 w, and ≥37w. PE and FGR were used as outcomes in logistic regression models. Area under the receiver operating characteristic (ROC) curve (AUC) of each PVI was calculated, cut-off points were determined to calculate the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), positive likelihood ratio (PLR), and negative likelihood ratio (NLR). Finally, AUCs combined with baseline characteristics, uterine artery pulsatility index (UTPI) and PVIs were used to determine whether PVIs could increase the predictive value. Results: Adverse outcomes occurred in 10.9% of pregnancies. Statistical differences appeared in 32–36 +6 w only. AUCs of vascularization index (VI) and vascularization flow index (VFI) for 32–36 +6 w were 0.79 (0.70–0.87, p: 0.000), and 0.78 (0.69–0.88, p: 0.000). Sensitivity, specificity, PPV, NPV, PLR, and NLR for VI were 0.91, 0.63, 20%, 98%, 2.39, and 0.15, and those for VFI were 0.62, 0.84, 29%, 95%, 3.75, and 0.45. AUC increased from 0.79 to 0.85 by adding PVIs to baseline characteristics and UTPI model. No statistical significance was found before 32w. Discussion: VI and VFI were valuable for predicting PE and FGR at the 32–36 +6 w stage, while their values before 32w were poor. Highlights: A prospective study of PVIs for predicting PE and FGR in a high-risk population. Assess the value of PVIs for predicting PE and FGR from 11 to 13 +6 w to term. PVIs could increase the predictive value in 32–36 +6 w.